PELATIHAN PENULISAN KARYA ILMIAH PADA MUSYAWARAH GURU MATA PELAJARAN (MGMP) BAHASA INDONESIA DI SMA/SMK KOTA BENGKULU - Nafri Yanti; Fina Hiasa; Arono Arono (Universitas Bengkulu, 2018)
Initial identification results to the MGMP Indonesian Bengkulu city, it is known that the main problem faced by most teachers is the difficulty to meet Minister of Manpower No. 16 of 2009 and Minister of Education Number 3/V/PB/2010 regarding the obligation of teachers to have publication of scientific papers if want to propose promotion from class 3A. This devotion activity is an effort to overcome the problem. The motives performed in this devotion are lectures, discussions and exercises. Based on hail training, it is known that there is an increase of trainee knowledge on the aspect of understanding on the structure and technique of writing scientific papers by 43%, scientific writing writing tips by 49%, reference information on scientific writing as much as 70% and information about 77% publication. Keywords: training, scientific work, MGMP